Analysis of water quality parameters in foothill rivers in the context of the construction of dam reservoirs - Połomski, Maksymilian; Wiatkowski, Mirosław; Tomczyk, Paweł (Frontiers in Environmental Science, 2026)
Backwater in retention reservoirs is potentially exposed to various contaminants, such as nutrients or heavy metals. Therefore, actions performed at the construction planning stage for such a facility are crucial; they are aimed at precisely evaluating the river’s physical and chemical potential, forecasting the process of eutrophication in the reservoir, and adopting appropriate engineering solutions to reduce the undesired deterioration in the quality of backwater. The aim of this study was to assess the physical and chemical conditions of selected rivers in the context of planned retention reservoirs and to evaluate the risk of water quality deterioration after impoundment. The study was conducted in the Ścinawka and Włodzica rivers in southwestern Poland, where the construction of storage reservoirs was considered. Water samples were taken at monthly intervals from March 2023 to March 2025 along the entire length of the running waters: from their springs to the location of the planned barrier, where bottom sediments were also examined. The applied methods included the analysis of physical and chemical parameters of water and bottom sediments. All physical and chemical parameters were summarised, and their concentrations were evaluated on the basis of national regulations; correlations of the parameters were analysed; and their variability in space and time was presented. Moreover, the size distribution of the components of bottom sediments and their richness in carbon, nitrogen and heavy metals were identified. The results showed that the contamination of water in the selected rivers results mainly from high concentrations of nitrogen and phosphorus compounds, which causes a high risk of eutrophication in hypothetical reservoirs. According to the Vollenweider model and the Benndorf modification, both reservoirs were classified as eutrophic. The analysis indicates that the hazard related to other physical and chemical parameters (oxygen, organic matter, salinity, mineralisation, suspended matter, metals) is moderate; however, the reservoirs should be designed with regard to the risk of episodic oxygen deficiency and a potential for silting up and load accumulation.